2017
DOI: 10.1186/s12863-017-0524-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic variability in Mexican chicken population using copy number variants

Abstract: BackgroundCopy number variations are genome polymorphism that influence phenotypic variation and are an important source of genetic variation in populations. The aim of this study was to investigate genetic variability in the Mexican Creole chicken population using CNVs.ResultsThe Hidden Markov Model of the PennCNV software detected a total of 1924 CNVs in the genome of the 256 samples processed with Axiom® Genome-Wide Chicken Genotyping Array (Affymetrix). The mapped CNVs comprised 1538 gains and 386 losses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
57
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(71 citation statements)
references
References 46 publications
12
57
2
Order By: Relevance
“…This difference was not surprising, as the genomic coverage of SNP chips is poor, which results in the detection of longer CNVRs [17,18]. The CNVRs detected in this study accounted for 2.17% of the sheep reference genome, which falls within the range (0.8%-5.12%) reported for horses, pigs, cattle and chickens [19][20][21][22]. However, the CNVRs identified in individual species accounted for more than 10% of their reference genomes, which may be related to the different genetic backgrounds of the studied animals [23,24].…”
Section: Discussionsupporting
confidence: 55%
“…This difference was not surprising, as the genomic coverage of SNP chips is poor, which results in the detection of longer CNVRs [17,18]. The CNVRs detected in this study accounted for 2.17% of the sheep reference genome, which falls within the range (0.8%-5.12%) reported for horses, pigs, cattle and chickens [19][20][21][22]. However, the CNVRs identified in individual species accounted for more than 10% of their reference genomes, which may be related to the different genetic backgrounds of the studied animals [23,24].…”
Section: Discussionsupporting
confidence: 55%
“…Elferink [16] found that a segment comprising a chicken prolactin receptor in the Z-chromosome is associated with the growth of the chickenundefineds fast-andslow feather. Gorla [17] provided that a chicken CNV map based on the 600 K SNP chip array jointly with a genome-wide gene copy number estimates in a native chicken population. Other reports have shown two copy number variable genes associated with Marek's disease, namely frizzled family receptor 6 (FZD6) and LIM and senescent cell antigen-like domain 1 (LIMS1) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, different algorithms can display variable sensitivity, consistency and reproducibility (ZHANG et al, 2014b). Nevertheless, PennCNV (WANG et al, 2007) was widely used in previous studies in different species, such as in horse (DUPUIS et al, 2013), pig (CHEN et al, 2012DONG et al, 2015;LONG et al, 2016;SCHIAVO et al, 2014;WANG et al, 2013WANG et al, , 2014, cattle (DA SILVA et al, 2016;DE ALMEIDA SANTANA et al, 2016;DURÁN AGUILAR et al, 2017;MCDANELD et al, 2014;WANG et al, 2015), sheep (LIU et al, 2013, including chicken (GORLA et al, 2017;JIA et al, 2013;RAO et al, 2016;ZHANG et al, 2014a;ZHOU et al, 2014), and display a better consistence in comparison with other algorithms (ZHANG et al, 2014b). Moreover, PennCNV is designed for CNV calling using parentsoffspring trios (WANG et al, 2008), which allows higher confidence for detection of inherited and de novo CNVs in populations with known family structure.…”
Section: Identification Of Cnvmentioning
confidence: 99%
“…CNV identification studies from SNP chips in chickens were performed using the Illumina 60K BeadChip developed by Groenen et al (2011) (JIA et al, 2013ZHANG et al, 2014b) and using the high density SNP chip available for the domestic chicken (Affymetrix 600K) developed by Kranis et al (2013) (GORLA et al, 2017YI et al, 2015).…”
Section: Copy Number Variations In the Chicken Genomementioning
confidence: 99%
See 1 more Smart Citation